The Relationship Between Social Media Use and Athlete Mental Health: A Literature Review - Gurning, Nico Febrian; Simbolon, Rifaldo Patriot; Rizqiansyah, Ridho; Sembiring, Revaldo; Elmahdi, Ody Pratama (Pusat Pengembangan Olahraga Universitas Pahlawan, 2025)
Purpose of the study: This systematic literature review examines the relationship between social media use and mental health outcomes among competitive athletes across various sports disciplines. The study aims to synthesize existing research to understand how social media platforms impact athlete psychological well-being, performance anxiety, and overall mental health. Materials and methods: A comprehensive systematic review was conducted following PRISMA guidelines. Electronic databases including PubMed, PsycINFO, SPORTDiscus, and Web of Science were searched from January 2015 to December 2024. Search terms included combinations of